2018
DOI: 10.1039/c7ra09183d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative SPECT imaging and biodistribution point to molecular weight independent tumor uptake for some long-circulating polymer nanocarriers

Abstract: Polymeric nanocarriers are promising entities for cancer diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…In order to evaluate the long-term stability of the 89 Zr-THPN radiocomplex and compare the ligand with the hydroxamic acid-based literature chelators DFO and DFO*, high-molecular weight (∼800 kDa) hyperbranched polyglycerol (HPG) was selected as carrier. HPG particles are highly biocompatible and can be readily synthesized as globular macromolecules with narrow size distributions. They have been investigated for a number of applications including as drug delivery vehicles, blood plasma expanders, cell surface protectants, or carriers for diagnostic imaging agents. ,, We reasoned that the long circulation half-life of high-molecular weight HPG would render these polymeric macromolecules also suitable carriers to investigate the long-term in vivo stability of attached radiochelates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the long-term stability of the 89 Zr-THPN radiocomplex and compare the ligand with the hydroxamic acid-based literature chelators DFO and DFO*, high-molecular weight (∼800 kDa) hyperbranched polyglycerol (HPG) was selected as carrier. HPG particles are highly biocompatible and can be readily synthesized as globular macromolecules with narrow size distributions. They have been investigated for a number of applications including as drug delivery vehicles, blood plasma expanders, cell surface protectants, or carriers for diagnostic imaging agents. ,, We reasoned that the long circulation half-life of high-molecular weight HPG would render these polymeric macromolecules also suitable carriers to investigate the long-term in vivo stability of attached radiochelates.…”
Section: Resultsmentioning
confidence: 99%
“…49−55 They have been investigated for a number of applications including as drug delivery vehicles, 56 blood plasma expanders, 57 cell surface protectants, 58 or carriers for diagnostic imaging agents. 54,55,59 We reasoned that the long circulation half-life of high-molecular weight HPG would render these polymeric macromolecules also HPG-chelator solutions of either of the three chelators (THPN, DFO, or DFO*) were then radiolabeled at ambient temperature with 89 Zr-oxalate solutions (∼32 MBq, ∼870 μCi). Once analysis by instant thin-layer chromatography (ITLC) indicated quantitative radiolabeling, reaction mixtures were purified by SEC and the radioconjugates were recovered in 97% radiochemical yield for all three conjugates.…”
mentioning
confidence: 99%
“…High molecular weight will ensure that HPG possesses a large hydrodynamic size, enhanced vascular retention, and the presence of an extensive number of functional groups [15]. Schmitt et al, showed the dependency of the blood circulation of nanocarriers on HPGs molecular weight [18]. They tested various molecular weight HPGs nanocarriers (25-500 kDa) covalently linked to chelator desferrioxamine (DFO) and radiolabeled with the gamma emitter 67 Ga [18].…”
Section: Linear Polyglycidolmentioning
confidence: 99%
“…Schmitt et al, showed the dependency of the blood circulation of nanocarriers on HPGs molecular weight [18]. They tested various molecular weight HPGs nanocarriers (25-500 kDa) covalently linked to chelator desferrioxamine (DFO) and radiolabeled with the gamma emitter 67 Ga [18]. Using qSPECT/CT imagining inside the heart of Rag2m mice, they proved that the blood circulation half-lives of the 67 Ga labeled HPGs increase from 9.9 to 47.8 h with increasing molecular weight [18].…”
Section: Linear Polyglycidolmentioning
confidence: 99%
See 1 more Smart Citation